Renewable Energy Sources in the EU Countries in the Concept of Sustainable Development in the Light of Statistical Multivariate Analysis - Krzysztof ZIOLO; Lidia LUTY; Danuta BOGOCZ; Monika ZIOLO (Communications of International Proceedings, 2021)
The increase in energy consumption in European countries causes an increase in greenhouse gas emissions to the atmosphere. Sustainable energy management is undoubtedly associated with the increased use of renewable energy sources ensuring energy security, diversification of energy supplies, supporting and improving the quality of the environment. The consequence of increasing air pollution is the decision of the European Commission to introduce a special directive aimed at taking measures to reduce air pollution. Renewable energy sources play a significant role in the pursuit of sustainable development, which has been taken into account in the sustainable development goals of the 2030 Agenda. The aim of the article is to present the diversity of the European Union countries in terms of activities undertaken as part of achieving the sustainable development goals affecting renewable energy sources. Methodology: In the preparation of the ranking of EU countries in 2010 and 2019, selected indicators were used to assess the implementation of the sustainable development goals and related to renewable energy sources. Due to the different names of the selected features, the results were normalized with zero unitarisation. Findings: The highest places in both rankings were taken by Sweden, Finland and Denmark, which for years have been pursuing a policy aimed at reducing greenhouse gas emissions and increasing the share of RES in the energy mix. The lowest positions in the ranking were taken by countries from the Visegrad Group, whose power industry is largely based on conventional sources. Research implications: There is a need to intensify efforts in the most vulnerable countries in order to increase spending on climate protection and move away from environmentally harmful energy sources.
Keywords: renewable energy sources; sustainable development; European Union countries